Systematic review of the efficacy of fat grafting and platelet‐rich plasma for wound healing. Issue 4 (9th May 2018) - Smith, Oliver J; Kanapathy, Muholan; Khajuria, Ankur; Prokopenko, Max; Hachach‐Haram, Nadine; Mann, Haroon; Mosahebi, Ash
Abstract : Adipose‐derived stem cells found in fat grafts may have significant healing properties. When fat is combined with autologous platelet‐rich plasma (PRP), there may be enhanced healing effects due to the pro‐angiogenic and anti‐inflammatory effects of PRP. This study aimed to evaluate the current evidence on fat grafting in combination with PRP for wound healing to establish the efficacy of this technique. A comprehensive search in the MEDLINE, EMBASE, CENTRAL, Science Citation Index, and Google Scholar databases (to March 2017) was conducted to identify studies on fat grafting and PRP for wound healing. Case series of less than 3 cases and studies only describing harvest technique were excluded. The database identified 571 articles, of which 3 articles that used a combination of fat and PRP for wound healing (1 RCT and 2 case series) were included in this review. A total of 69 wounds in 64 patients were treated with an average wound size of 36.32cm 2 . Of these, 67% of wounds achieved complete healing. When reported, the mean time to healing was 7.5 weeks for those who underwent a single treatment. There were no significant complications in any patients. The combination of fat grafting and PRP may achieve adequate wound healing with relatively quick wound healing time compared with standard wound management options. However, evidence is extremely limited, and further studies are required to evaluate its efficacy for wound healing.